2020
DOI: 10.1038/s41586-020-2777-8
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback control of neuronal activity by microglia

Abstract: Microglia, the brain’s resident macrophages, help to regulate brain function by removing dying neurons, pruning non-functional synapses, and producing ligands that support neuronal survival 1 . Here we show that microglia are also critical modulators of neuronal activity and associated behavioural responses in mice. Microglia respond to neuronal activation by suppressing neuronal activity, and ablation of microglia amplifies and synchronizes the activity of neurons, leading to seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
555
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 630 publications
(628 citation statements)
references
References 99 publications
(157 reference statements)
29
555
2
Order By: Relevance
“…We reject the comment by Green and Hume ( 4 ) that PLX5622 dose and duration was not provided or that it was selected arbitrarily. A careful reading of our paper ( 1 ) and the literature reveals this information, which is in concordance with at least 14 papers using exactly the same dose (PLX5622 chow, 1,200 ppm) and duration (3 wk) ( 1 3 , 5 ), some of which have been cited by Green et al ( 6 ) in a prior review. † For the benefit of the community, we provide additional data in this Reply showing that even short-term (7 d or 10 d) treatment with PLX5622 results in similar nonmicroglia changes ( Figs.…”
supporting
confidence: 82%
“…We reject the comment by Green and Hume ( 4 ) that PLX5622 dose and duration was not provided or that it was selected arbitrarily. A careful reading of our paper ( 1 ) and the literature reveals this information, which is in concordance with at least 14 papers using exactly the same dose (PLX5622 chow, 1,200 ppm) and duration (3 wk) ( 1 3 , 5 ), some of which have been cited by Green et al ( 6 ) in a prior review. † For the benefit of the community, we provide additional data in this Reply showing that even short-term (7 d or 10 d) treatment with PLX5622 results in similar nonmicroglia changes ( Figs.…”
supporting
confidence: 82%
“…The inflammatory response after cerebral ischemia-reperfusion (I/R) is characterized by the activation and polarization of resident microglia/macrophage ( Badimon et al, 2020 ), whose dynamic polarization state plays a dual role in brain injury and repair ( Kanazawa et al, 2017 ). Although there is controversy ( Ransohoff, 2016 ), it is generally believed that after stroke, microglia/macrophage are polarized into the pro-inflammatory (M1) phenotype and anti-inflammatory (M2) phenotype ( Yang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence demonstrates that microglia influence neuronal excitability and seizure susceptibility ( Badimon et al, 2020 ; Umpierre et al, 2020 ; Wu et al, 2020 ). We found that excessive activation of mTOR in TSC1-deficient mice leads to severe spontaneous seizures, involving a noninflammatory mechanism ( Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%